An Analysis of the Relationship of Saṃsāra in Theravada Buddhism - Pongsakollawat , Yannawadee (Journal of Buddhist Studies, 2023)
The research paper has two goals: i) to examine Sasra in Theravada Buddhism, and 2) to assess Sasraís connection in Theravada Buddhism. This study employed with a documentary study. The studyís findings indicated that: 1) Saṃsāra in Theravada Buddhism means wandering around in samsaric sympathy, which is the cycle of rebirth in the many realms of beings under the influence of defilements, kamma, and rotating in such a way if it is not cut off. Defilements, karma, and barriers are unstoppable, as is the cycle of life and birth for all beings. It centres around never-ending cycles. ìMonks, this round of Saṃsāra is endless,î stated the Buddha. When uneducated beings are the hurdles, and passion is a component, they move to and from the most primitive stages. Every human being falls into the Saṃsāra cycle. In other words, when there is defilement, both good and evil deeds are regarded kamma, and while practicing kamma, there must be repercussions. There is always a kammaís effect. The three components of the Saṃsāra cycle defilements, karma, and obstacles are the body, speech, and mind. 2) The cycle of Saṃsāra is inextricably linked with the ideas of the path, consequences, and Nibbana. Because human life is cyclical, i.e., it emerges, exists, and dies, it is known as the 9 Lokuttara-dhamma: supermundane states. The reason why humans must cycle, and die is that they are born indefinitely. Because Saṃsāra ës cycle has not been cut in accordance with the Threefold Rule, namely morality, concentration, and wisdom. There are two basic meditation principles: Samatha meditation and Vipassana meditation.